Have Irish sovereign bonds decoupled from the euro area periphery, and why? - David Cronin; Peter G. Dunne; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2019)
This paper considers whether Ireland's sovereign bonds have decoupled from other euro area sovereigns (Portugal, Italy, Greece and Spain - the "periphery") with whom it was categorised during the sovereign bond market crisis of the early 2010s. Having initially reviewed yield and sovereign stress indicator data, two econometric methodologies (those of Gibson et al., 2017, and Diebold and Yilmaz, 2012) are applied to long-term bond spread data for the euro area 11 countries for the period March 2005 to July 2018. These indicate a shift since around mid-2013 in the Irish sovereign bond market's relationships within the euro area, with a higher correlation and interaction with developments in "core" member states' markets over those of the periphery member states now occurring. An econometric model of the determination of Irish sovereign bond yield spread shows the trend decline in its value since the early 2010s owing to both an improvement in the sustainability of the fiscal position and undue market pessimism dissipating over time. The paper concludes that a combination of emerging fiscal and financial sector vulnerabilities can lead quickly to an upsurge in the sovereign's market bond yields that is justified by these developments and which can be added to by financial markets' tendency to move quickly from a state of undue optimism to undue pessimism. In such an environment, maintaining a sustainable fiscal path, adhering to fiscal rules, and fostering a resilient banking system are the best means by which the sovereign can help to keep its bond yields from being priced too highly and from varying substantially over time.
Keywords: 330